Conocimientos sobre cáncer oral en estudiantes de Medicina y Odontología. Universidad Nacional de Chimborazo, 2022 - María José, Ñacato Llamuca (2023)
ABSTRACT: The lack of knowledge of oral cancer by health professionals is the main cause of delay in prevention, diagnosis and treatment. Therefore, the objective of the present study was to determine the knowledge about oral cancer among ninth and tenth semester medical and dental students of the National University of Chimborazo. A descriptive cross-sectional study was carried out with a study population of 142 students. The technique used was the survey and the instrument was the questionnaire, which was made in Microsoft Forms and consists of 19 polytomous questions. The data were processed in the SPSS v25 program. In general, 52.8 % of the study group presented a deficient level of knowledge, 41.5 % regular and only 5.6 % a good knowledge, in which it was observed that 53 % of the dental students presented a regular level of knowledge in comparison with the medical career whose level of knowledge was deficient in 64 % of students, the non-parametric Mann-Whitney U test was used which denoted statistically significant differences between the two study groups. Knowledge about oral cancer should be reinforced throughout university preparation in medicine and dentistry emphasizing the importance of prevention and early diagnosis of potentially malignant lesions and oral cancer.